INTEGRATION OF SOFTWARE SOLUTIONS VIA AN INTERMEDIARY WEB SERVICE - P. Milev (Trakia Journal of Sciences)
The article examines issues, related to the integration of software solutions. In this sense, the paper presents features of information systems with multilayered architecture. The integration of the individual physical layers of the system is the most important issue for these software solutions. The main purpose of the article is to explore the possibilities for realization of such integration and to present a conceptual model for communication between the different layers of an information system through an intermediary web service. To achieve its goal, the article uses various scientific methods, including study, analysis, research, modeling and experimentation. The results of this paper support the main hypothesis of the study, namely defining the advantages of integrating information systems with the help of an intermediary software service. The conclusion highlights the possibilities for improvement of communication between different physical layers of software solutions with distributed business logic.